The Influence of Spiritual Therapy and Relaxation on Anxiety in the Elderly During Health Crises - Kamaruzzaman, Abdi; Hidayati, Ulfah (Indonesian Journal of Islamic Counseling, 2024)
This article aims to investigate the effectiveness of combining dzikir (Islamic remembrance) and progressive muscle relaxation therapy in reducing anxiety among the elderly. The study employs a mixed-methods approach with a quasi-experimental design for the quantitative aspect and semi-structured interviews for the qualitative aspect. The respondents consist of 50 elderly individuals experiencing moderate to severe anxiety. Data collection was conducted through surveys using the Geriatric Anxiety Scale and in-depth interviews. The results indicate that the combined intervention significantly reduced anxiety levels, with 60% of the elderly experiencing a reduction from moderate to mild anxiety. Additionally, 50% of the respondents reported improved sleep quality after undergoing therapy. Social support was also found to play a crucial role in moderating anxiety reduction, with those receiving higher levels of social support showing more significant decreases in anxiety. This study highlights the importance of a holistic approach that encompasses physical, psychological, and spiritual aspects in managing anxiety among the elderly. The findings contribute valuable insights for developing more comprehensive mental health programs for the elderly.